Integrating Indigenous Knowledge into Quality Assurance Standards in Multicultural Classrooms - Lune Mille; Faht Ben Josh (International Journal of Post Axial: Futuristic Teaching and Learning, 2025)
This study explores the integration of Indigenous Knowledge into quality assurance (QA) standards in multicultural classrooms, focusing on how localized epistemologies can enhance educational relevance and inclusivity. Amid the global push for standardized QA frameworks, many such models overlook the cultural wealth and pedagogical insights rooted in Indigenous traditions, particularly in diverse educational settings. Using a qualitative case study approach, the research investigates how schools in multicultural regions embed Indigenous values, practices, and knowledge systems into their teaching, learning, and assessment processes. Data were collected through interviews with teachers, school leaders, and community elders, as well as through classroom observations and document analysis. The findings reveal that integrating Indigenous Knowledge into QA processes fosters greater cultural affirmation, increases student engagement, and promotes contextually grounded standards of excellence. However, the process is not without challenges, such as policy misalignment, lack of teacher training, and tensions between standardized assessment criteria and culturally responsive pedagogies. The study concludes that for QA to be truly equitable and inclusive, it must move beyond universal benchmarks and instead adopt a flexible, context-sensitive approach that honors the lived realities of Indigenous and minority students.